Enhancement of the IceCube surface instrumentation by a hybrid radio and scintillation detector array - IceCube Collaboration; Shefali, Shefali (Scuola Internazionale Superiore di Studi Avanzati, 2022)
The IceCube Neutrino Observatory is a cubic kilometer scale detector deployed in the antarctic ice, capable of detecting neutrinos of energies ranging from approximately 10 GeV to PeV and above. In addition to being a powerful neutrino observatory, IceCube is extensively involved in cosmic ray physics. The surface array of IceCube, IceTop, consisting of frozen water tanks equipped with photomultipliers, detects secondary particles like electrons, protons and muons from cosmic ray air showers of energies up to 1 EeV. In addition, it is also used to function as a veto for the astrophysical neutrino searches and calibration detector for the IceCube in-ice instrumentation. Despite the valuable scientific results obtained so far, the snow accumulation on top of these detectors contributes to an increased energy uncertainty in the detected signals, and consequently, the shower reconstruction. Moreover, improvements to the array are needed to understand the astrophysics of the high-energy cosmic-ray sky. Enhancing IceTop with a hybrid array of scintillation detectors and radio antennas will lower the energy threshold for air-shower measurements, provide more efficient veto capabilities, enable the separation of the electromagnetic and muonic shower components and improve the detector calibration by compensating for snow accumulation. Following the success of the first prototype station consisting of three radio antennas and eight scintillation detectors deployed at the South Pole in 2018, the production of detectors for a total 32 stations is ongoing. The deployment status, calibration methods, and science goals of the enhancement will be discussed in this contribution.